Physical activity and sedentary time in Physical Education classes and their association with cardiorespiratory fitness in students - Maziero,Renato Silva Barbosa (2017)
This study aimed to evaluate the intensity and duration of activities in Physical Education classes and to test their association with cardiorespiratory fitness. It is a cross-sectional study with 614 schoolchildren (51% girls), aged 10 to 17 years old, evaluated by accelerometers in 100 Physical Education classes in Pinhais, Southern Brazil. The intensity of the activities was determined by accelerometry (Actigraph, model WGT3X). The time spent in each intensity (sedentary, light, moderate, intense and very intense) was evaluated. Cardiorespiratory fitness was determined by the Léger test 20 meters. The average duration of the classes was 31.5 minutes (SD = 4.3). On average, boys and girls passed 23.8% and 16.9% (p <0.05) of a class in activities of moderate and vigorous intensity, respectively. The correlation between time in physical activity and cardiorespiratory fitness was significant in boys (Light, moderate and vigorous, respectively: r = 0.12, p = 0.04, r = 0.12, p = 0.04, r = 0.15, p = 0.009). In conclusion, the low correlation between physical activity time in Physical Education classes and cardiorespiratory fitness reinforces the discussion about how this subject can contribute to the public health in young population.